Multidimensional Approach to Frailty - Wleklik, Marta; Uchmanowicz, Izabella; Jankowska, Ewa A.; Vitale, Cristiana; Lisiak, Magdalena; Drozd, Marcin; Pobrotyn, Piotr; Tkaczyszyn, Michał; Lee, Christopher (Frontiers in Psychology, 2020)
The concept of FS was first described in the scientific literature three decades ago. For a very long time we understood it as a geriatric problem, recently becoming one of the dominant concepts in cardiology. It identifies symptoms of FS in 1 in 10 elderly people. It is estimated that in Europe, 17% of elderly people have FS. The changes in FS resemble and often overlap with changes associated with the physiological ageing process of the body. Although there are numerous scientific reports confirming that FS is age correlated, it is not an unavoidable part of the ageing process and does not apply only to the elderly. FS is a reversible clinical condition. To maximize benefits of frailty-reversing activities for patient with frailty, identification of its determinants appears to be fundamental. Many of the determinants of the frailty syndrome have already been known: reduction in physical activity, malnutrition, sarcopenia, polypharmacy, depressive symptom, cognitive disorders, lack of social support. This review shows that insight into FS determinants is the starting point for building both the comprehensive definition of FS and the adoption of the assessment method of FS, and then successful clinical management.